The lipid metabolism in carp during invasion by the tapeworn Bothriocephalus acheilognathi - L. L. Yuskiv; I. D. Yuskiv (Regulatory Mechanisms in Biosystems, 2020)
The changes in total lipids, their fatty acid composition and the ratio of individual classes were established in tissues of the intestine, hepatopancreas and skeletal muscles of carp (Cyprinus carpio Linnaeus, 1758), with body weight 14.5–20.5 g, at different rates of invasion by Bothriocephalus acheilognathi (Yamaguti, 1934) helminth, which belongs to the family Bothriocephalidae, of the Pseudophyllidae order, of the Cestoda class. The examined carp was divided into three groups: first group of fish was free from intestinal helminths of B. acheilognathi (control); second group of fish was weakly infected with helminths (intensity of invasion is 1–3 helminths per fish); the third group of fish was highly infected (the invasion intensity is 4 worms and more per fish). Our results showed that fish infected with helminth B. acheilognathi compared to uninfected fish had reduced total lipid level in the gut due to phospholipids, triacylglycerols, and also lipids were characterized by lower content of linoleic, linolenic, arachidonic, penta- and hexanoic fatty acids; decrease in the level of unsaturated and increase in the content of saturated fatty acids, which leads to an increase of the saturation factor. During the infection of carp with B. acheilognathi in the hepatopancreas, the content of total lipids, structural lipids – phospholipids and reserve energy sources – triacylglycerols is probably reduced, and lipids are characterized by a high content of saturated fatty acids (С14:0, С16:0, С18:0) and lower content of unsaturated: arachidonic (С20:4), linolenic (С18:3) and linoleic acid (С18:2), which is associated with a decrease in the source for the synthesis of a number of polyunsaturated fatty acids, especially docosahexaenoic (С22:6). The total content of lipids, triacylglycerols, free fatty acids and phospholipids in skeletal muscle of carp during the Bothriocephalus invasion decreased and the content of free cholesterol, mono- and triacylglycerols increased. Helminth B. acheilognathi has the effect of reducing the total lipids of the skeletal muscle content of С18-, С20-, С22-polyunsaturated fatty acids and increasing the content of saturated (С14:0, С16:0, С18:0) and monounsaturated (С16:1, С18:1) fatty acids. The obtained results prove that the parasite B. acheilognathi in the intestine of the carp significantly affects the nutrition processes of the host depending on the intensity of the damage by helminths, which is accompanied by impaired lipid metabolism.